Users’ Perception of University Library Resources and Services in South East Zone of Nigeria - Nkechi, Obiozor-Ekeze Roseline (Scientific Research, 2015)
This study seeks to determine how users of the university libraries perceive the services rendered to them. Department of Mechanical Engineering was chosen as the population of this study. It is heavily populated with students seeking for information. 600 copies of questionnaire were made, only 450 copies were returned, well-filled, that is 75% of the questionnaire. Results were gathered and findings were made. The result showed that University Libraries are underfunded, they lack qualified personnel and also the university libraries do not have a general standard that guild them to access if actually users of the libraries are satisfied with the library or not.
Keywords: University Libraries; Information Services; Department of Mechanical Engineering; Students; Standards; South East of Nigeria